2018
DOI: 10.1016/j.applanim.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

A spatial discounting test to assess impulsivity in dogs

Abstract: In domestic dog's trait impulsivity can be measured psychometrically using the Dog Impulsivity Assessment Scale (DIAS) and experimentally using a temporal discounting paradigm which requires substantial training. A Spatial Discounting Task (SDT) was developed as an alternative experimental method to assess impulsivity, and evaluated performance in adult (2-10 years) and younger (2-9 months) dogs. The test was modified for field use with fewer controls (Simplified Spatial Discounting Task (SDTs)). Convergent va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 36 publications
3
38
1
Order By: Relevance
“…Bray et al (2014) attribute this to context specificity in impulsivity, and this is likely accurate to some extent since we see evidence of similar context specificity in humans (Evenden, 1999). However, the fact that owner reports of dog impulsivity correlate with three different behavioral measures of impulsivity (Wright et al, 2012;Brucks et al, 2017;Brady et al, 2018) provides tantalizing evidence that there should be some form of a common underlying construct of impulsivity. Though we did not measure impulsivity behaviorally in this study, behavioral impulsivity would be an interesting measure for future studies, especially since it seems to be critical for many tasks in working dogs (Barrera et al, 2019;Tiira et al, 2020).…”
Section: Impulsivitysupporting
confidence: 52%
See 1 more Smart Citation
“…Bray et al (2014) attribute this to context specificity in impulsivity, and this is likely accurate to some extent since we see evidence of similar context specificity in humans (Evenden, 1999). However, the fact that owner reports of dog impulsivity correlate with three different behavioral measures of impulsivity (Wright et al, 2012;Brucks et al, 2017;Brady et al, 2018) provides tantalizing evidence that there should be some form of a common underlying construct of impulsivity. Though we did not measure impulsivity behaviorally in this study, behavioral impulsivity would be an interesting measure for future studies, especially since it seems to be critical for many tasks in working dogs (Barrera et al, 2019;Tiira et al, 2020).…”
Section: Impulsivitysupporting
confidence: 52%
“…For our measure of impulsivity in dogs, we used the Dog Impulsivity Assessment Scale (Wright et al, 2011), which is a validated, owner-report scale that has been shown to correlate with behavioral measures of impulsivity (Wright et al, 2012;Brucks et al, 2017;Brady et al, 2018)-though this is not always the case (Fagnani et al, 2016)-as well as physiological markers associated with impulsivity (Wright et al, 2012). We found that owner reports of dog problem behavior (Hiby et al, 2004) and dog disobedience (Bennett & Rohlf, 2007) predicted the impulsivity scores.…”
Section: Impulsivitymentioning
confidence: 99%
“…The scale was found to relate to variation in the behaviour observed in two systematically manipulated experimental designs, i.e. a delayed reward choice test (Wright et al, 2012) and, for the OQS and Factor 1, a spatial discounting test (Brady et al, 2018); correlations were found also between the DIAS scores and variation in physiological factors -i.e. serotonin metabolites (5-HIAA) levels (Wright et al, 2012).…”
Section: Introductionmentioning
confidence: 95%
“…Trait impulsivity may be measured in domestic dogs with questionnaire scales, such as the Dog Impulsivity Assessment Scale (DIAS; Wright et al, 2011). The DIAS provides an overall questionnaire score (OQS), which directly reflects the dog owner's opinion on how impulsive their dog is and resulted to be higher in dogs with behaviour problems (Wright et al, 2011) as well as behavioural measures (Brady et al, 2018). However, the scale also provides three independent sub-factors, which can reflect distinct nuanced features of dog impulsivity.…”
Section: Introductionmentioning
confidence: 99%
“…
1617 behavioural measures (Brady et al, 2018). However, the scale also provides three independent 44 sub-factors, which can reflect distinct nuanced features of dog impulsivity.
…”
mentioning
confidence: 99%